A Historical Analysis of Parapsychology Research Methodologies - Nicholas F. Andy & Dunlap H. Rhodes (International Journal of Innovative and Applied Finance, 2022)
This paper presents a comprehensive historical analysis of research methodologies employed in parapsychology from the early 20th century to the present. By examining key studies and their methodologies, the paper identifies trends, challenges, and advancements in the field. The analysis highlights the evolution of experimental designs and the ongoing debate regarding the scientific legitimacy of parapsychological research.